A Variational Method for Multivalued Boundary Value Problems - Droh Arsène Béhi; Assohoun Adjé (Abstract and Applied Analysis)
In this paper, we investigate the existence of solution for differential systems involving a ϕ−Laplacian operator which incorporates as a special case the well-known p−Laplacian operator. In this purpose, we use a variational method which relies on Szulkin’s critical point theory. We obtain the existence of solution when the corresponding Euler–Lagrange functional is coercive.